Safety of antiobesity drugs. (August 2013) - Cheung, Bernard Man Yung; Cheung, Tommy Tsang; Samaranayake, Nithushi Rajitha
Obesity is a major health problem worldwide. Although diet and physical activity are crucial in the management of obesity, the long-term success rate is low. Therefore antiobesity drugs are of great interest, especially when lifestyle modification has failed. As obesity is not an immediate life-threatening disease, these drugs are required to be safe. Antiobesity drugs that have been developed so far have limited efficacies and considerable adverse effects affecting tolerability and safety. Therefore, most antiobesity drugs have been withdrawn. Fenfluramine and dexfenfluramine were withdrawn because of the potential damage to heart valves. Sibutramine was associated with an increase in major adverse cardiovascular events in the Sibutramine Cardiovascular Outcomes (SCOUT) trial and it was withdrawn from the market in 2010. Rimonabant was withdrawn because of significant psychiatric adverse effects. Orlistat was approved in Europe and the United States for long-term treatment of obesity, but many patients cannot tolerate its gastrointestinal side effects. Phentermine and diethylpropion can only be used for less than 12 weeks because the long-term safety of these drugs is unknown. Ephedrine and caffeine are natural substances but the effects on weight reduction are modest. As a result there is a huge unmet need for effective and safe antiobesity drugs. Recently lorcaserin and topiramate plus phentermine have been approved for the treatment of obesity but long-term safety data are lacking.